Importance of peniscopy, oncologic cytology and histopathology in the diagnosis of penile infection by human papillomavirus - Nicolau, Sérgio Mancini; Martins, Nelson Valente; Ferraz, Paulo Eduardo; Stávale, João Norberto; Gonçalves, Wagner José; Baracat, Edmund Chada; Lima, Geraldo Rodrigues de (São Paulo Medical Journal, 1997)
INTRODUCTION: Male genital infection by human papillomavirus is of particular importance since it is often asymptomatic. The patient generally presents no clinical lesion. Therefore, men represent an important reservoir of virus, playing a special role in the transmission and perpetuation of the disease. PATIENTS AND METHODS: In the present prospective clinical trial study, 190 sex partners of women with genital infection by human papillomavirus, associated or not with cervical intraepithelial neoplasia, were investigated. All patients were unaware of or denied the presence of a genital lesion. RESULTS: Cytologic examination revealed koilocytosis in 9 cases (4.7%) in the urethra and in 3 cases (1.6%) in the corona of the glans and the distal prepuce. Peniscopy with the previous use of 5% acetic acid revealed white lesions in 97.9% of the patients. Toluidine blue stained most of the lesions. At least one fragment revealed koilocytosis in the histopathologic study of 97 cases (51.05%). CONCLUSION: The three methods complement one another, allowing a more precise diagnosis of this infection in men.